The effect of food consumption on lumefantrine bioavailability in African children receiving artemether-lumefantrine crushed or dispersible tablets (Coartem) for acute uncomplicated Plasmodium falciparum malaria - Borrmann, Steffen; Sallas, William M.; Machevo, Sonia; González, Raquel; Björkman, Anders; Mårtensson, Andreas; Hamel, Mary; Juma, Elizabeth; Peshu, Judy; Ogutu, Bernhards; Djimdé, Abdoulaye; D’Alessandro, Umberto; et al. (Tropical medicine & international health, 2010)
Objectives Artemether-lumefantrine (AL) is first-line treatment for uncomplicated malaria in many African countries. Concomitant food consumption may affect absorption of lumefantrine but data in the most important target population, i.e. children, are lacking. Therefore, we evaluated the effect of food intake on oral lumefantrine bioavailability in African children with malaria. Methods In a randomised, investigator-blinded, multicentre phase III efficacy trial, 899 infants and children with acute uncomplicated Plasmodium falciparum malaria received six doses of AL according to body weight over 3 days either as crushed tablets (Coartem®) or as dispersible tablets. Single blood samples were obtained for lumefantrine plasma concentration determination in a subset of 621 patients, and a two-compartment pharmacokinetic model was constructed. Results The mean observed lumefantrine plasma concentration for crushed tablet and dispersible tablet, respectively, was 100% and 55% higher with a concomitant meal at the time of dose intake than when taken alone. Similarly, consumption of milk (the most common meal) increased model-estimated lumefantrine bioavailability by 57% (90% CI: 29-96%) with crushed tablets and 65% (90% CI: 28-109%) with dispersible tablets compared to no food. The 28-day PCR-corrected cure rate (primary study endpoint) in the evaluable population was 582/587 [99.1% (95% CI: 98.0-99.7%)] and was not related to food intake. Conclusions AL was highly efficacious. Concomitant food intake increased lumefantrine absorption in children with malaria.
Gesehen am 09.02.2023